The Construction of Teacher’s Teaching Quality Evaluation System Based on the Teacher-Student Cooperation Model - He Xiaofei; Wang Yuning (SHS Web of Conferences, 2024)
Within the framework of advancing educational evaluation reform in the modern era, establishing a scientific and rational assessment system for the quality of teacher’s instruction holds immense importance. This contributes to the further development of autonomous evaluations within colleges and universities, fosters enhancements in higher education evaluation systems, and supports the modernization of higher education governance. Considering the evolving demands for cultivating excellence in higher education, the assessment of teachers’ instructional quality continues to face challenges, encompassing evaluation criteria, categorization guidelines, system enhancements, digital adaptation, and more. In the construction of a quality assessment system for teacher’s instruction in higher education, continuous optimization of the evaluation system for teaching quality is essential. This optimization should be driven by scientific principles, grounded in collaboration between teachers and students, and aligned with fundamental principles, including categorized assessment, process orientation, digital integration, and more.